Prove the following by induction on n:
∀ m ∈ N, ∀ n ∈ N( n ≥ m -> m|n!)
Hint: your "base" case will be at n = m.
I know what I want to show for the inductive step, I'm just having a difficult time writing it in proof form. So if we assume ∀ m ∈ N, ∀ n ∈ N( n ≥ m -> m|n!) is true then then n+1 case is true.
so n ≥ m ->m|(n+1)! I'm not sure if that when you show the n+1 case do you also show the right side of the implication as n+1?
So instead it would be n+1 ≥ m ->m|(n+1)! ?
I'm also unsure of how to do this one.
Prove the following by induction on n:
∀ m ∈ N, ∀ n ∈ N( m ≤ n -> m|n!)
Hint: (n + 1)! = (n + 1) (n!).
Hint: Carefully stating P(n) will make this much easier.
Note: I am aware that this sentence is equivalent to the previous problem., but the proofs are fairly
different, though.
∀ m ∈ N, ∀ n ∈ N( n ≥ m -> m|n!)
Hint: your "base" case will be at n = m.
I know what I want to show for the inductive step, I'm just having a difficult time writing it in proof form. So if we assume ∀ m ∈ N, ∀ n ∈ N( n ≥ m -> m|n!) is true then then n+1 case is true.
so n ≥ m ->m|(n+1)! I'm not sure if that when you show the n+1 case do you also show the right side of the implication as n+1?
So instead it would be n+1 ≥ m ->m|(n+1)! ?
I'm also unsure of how to do this one.
Prove the following by induction on n:
∀ m ∈ N, ∀ n ∈ N( m ≤ n -> m|n!)
Hint: (n + 1)! = (n + 1) (n!).
Hint: Carefully stating P(n) will make this much easier.
Note: I am aware that this sentence is equivalent to the previous problem., but the proofs are fairly
different, though.